2011
DOI: 10.1063/1.3599091
|View full text |Cite
|
Sign up to set email alerts
|

Cis-trans isomerization in the S1 state of acetylene: Identification of cis-well vibrational levels

Abstract: A systematic analysis of the S(1)-trans (Ã(1)A(u)) state of acetylene, using IR-UV double resonance along with one-photon fluorescence excitation spectra, has allowed assignment of at least part of every single vibrational state or polyad up to a vibrational energy of 4200 cm(-1). Four observed vibrational levels remain unassigned, for which no place can be found in the level structure of the trans-well. The most prominent of these lies at 46 175 cm(-1). Its (13)C isotope shift, exceptionally long radiative li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 42 publications
(104 reference statements)
1
22
0
Order By: Relevance
“…Several decades of spectroscopy performed by many workers, [1][2][3][4][5][6][7][8][9][10][11][12][13][14] as well as numerous theoretical studies, [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] have shown that the molecule is transbent, and have given a complete vibrational assignment up to 4500 cm −1 of vibrational energy. A second conformer, where the molecule is cis-bent, was discovered recently.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several decades of spectroscopy performed by many workers, [1][2][3][4][5][6][7][8][9][10][11][12][13][14] as well as numerous theoretical studies, [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] have shown that the molecule is transbent, and have given a complete vibrational assignment up to 4500 cm −1 of vibrational energy. A second conformer, where the molecule is cis-bent, was discovered recently.…”
Section: Introductionmentioning
confidence: 99%
“…A second conformer, where the molecule is cis-bent, was discovered recently. 13 It lies 2670 ± 10 cm −1 above the trans conformer, 34 and the barrier to isomerization is estimated to lie 4979 cm −1 (plus or minus a few hundred cm −1 ) above the trans minimum. 33 Since the S 1 -cis state transforms as A 2 in the C 2v point group, transitions to it from the + g electronic ground state are dipole-forbidden.…”
Section: Introductionmentioning
confidence: 99%
“…66,68 There are three fundamental bending vibrations of cis-S 1 , with symmetry a 2 , b 2 , a 1 , as shown in Fig. 12.…”
Section: Description Of Cis-s 1 Bending Spectrummentioning
confidence: 99%
“…Further detailed analyses by Watson et al, [5][6][7] the Crim group, 8,9 Yamakita and Tsuchiya, [10][11][12] and Merer et al [13][14][15][16][17] have led to an essentially complete assignment of the vibrational and rotational structure up to 4500 cm −1 above the zero-point level of theà state. One of the most interesting results of these analyses has been the discovery 17,18 of bands that belong to the cis-bent isomer of theà state, the zero-point level of which lies about 2670 cm −1 higher in energy than that of the trans-bent isomer. The existence of the cis isomer had been predicted by several theoretical studies, [19][20][21][22][23][24] but it was thought that theà state of the cis isomer would be unobservable because it transforms as 1 A 2 in the C 2v point group; thus, transitions to it from the 1 Σ + g ground state are electric dipole forbidden.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, interactions occur between cis and trans levels at similar energies. 18,28,30 These are the mechanisms by which the cis levels obtain their intensity by mixing with nearby trans levels, though the selection rules and level shifts are different for even and odd K-values. Combining these two effects, the resulting K-staggering varies in a seemingly random fashion from level to level.…”
Section: Introductionmentioning
confidence: 99%